Biomarkers of mercury toxicity: Past, present, and future trends. (3rd April 2017) - Branco, Vasco; Caito, Sam; Farina, Marcelo; Teixeira da Rocha, João; Aschner, Michael; Carvalho, Cristina
ABSTRACT: Mercury (Hg) toxicity continues to represent a global health concern. Given that human populations are mostly exposed to low chronic levels of mercurial compounds (methylmercury through fish, mercury vapor from dental amalgams, and ethylmercury from vaccines), the need for more sensitive and refined tools to assess the effects and/or susceptibility to adverse metal-mediated health risks remains. Traditional biomarkers, such as hair or blood Hg levels, are practical and provide a reliable measure of exposure, but given intra-population variability, it is difficult to establish accurate cause–effect relationships. It is therefore important to identify and validate biomarkers that are predictive of early adverse effects prior to adverse health outcomes becoming irreversible. This review describes the predominant biomarkers used by toxicologists and epidemiologists to evaluate exposure, effect and susceptibility to Hg compounds, weighing on their advantages and disadvantages. Most importantly, and in light of recent findings on the molecular mechanisms underlying Hg-mediated toxicity, potential novel biomarkers that might be predictive of toxic effect are presented, and the applicability of these parameters in risk assessment is examined.